Boundary Layer Flow and Heat Transfer past a Permeable Shrinking Sheet in a Nanofluid with Radiation Effect. (23rd December 2012) - Zaimi, Khairy; Ishak, Anuar; Pop, Ioan
Abstract : The steady two-dimensional boundary layer flow of a nanofluid over a shrinking sheet with thermal radiation and suction effects is studied. The resulting system of ordinary differential equations is solved numerically using a shooting method for three different types of nanoparticles, namely, copper (Cu), alumina (Al2 O3 ), and titania (TiO2 ). The results obtained for the velocity and temperature profiles as well as the skin friction coefficient and the local Nusselt number for some values of the governing parameters, namely, the nanoparticle volume fraction, shrinking, suction, and viscous dissipation parameters, are discussed. The numerical results show that dual solutions exist in a certain range of suction parameter.